Classification of Hepatitis Disease Using The Fuzzy Mamdani Method - Hidayani, Nurul; Muliono, Rizki (Universitas Medan Area, 2025)
In the modern world, almost everyone uses technology and information. This is evident in various fields, ranging from education and employment to entertainment. Society is too dependent on technology and information, to the point of neglecting their own health. There are many diseases caused by neglecting one's own health, one of which is hepatitis. This is because some people pay little attention and are reluctant to get it checked. Because hepatitis is very dangerous for human survival, treatment must begin as soon as the first symptoms appear and assist in the early diagnosis of hepatitis. This will allow for the identification of the type of hepatitis disease. The aim of this research is to apply the Mamdani fuzzy method for the classification of hepatitis diseases. The Mamdani fuzzy method has been successfully utilized in systems for diagnosing hepatitis diseases. In this system, it will provide instructions, namely to select which symptoms are experienced, then you can choose those symptoms by checking them off, and this system will provide a diagnosis based on the symptoms experienced. The diagnosis results include the type of hepatitis disease experienced, as well as treatment solutions. The results obtained for diagnosing hepatitis A disease using fuzzy Mamdani calculation shows that 68% , and the diagnosis of hepatitis B disease using fuzzy mamdani calculations shows 53% , and the diagnosis of hepatitis C disease using fuzzy mamdani calculations shows 59%.